Perbandingan Struktur Komunitas Cacing Tanah Megadrilli pada Ekosistem Alami dan Ekosistem Buatan - Jody, Regina; Darmi, Darmi; Rizwar, Rizwar; Jarulis, Jarulis; Wibowo, Risky Hadi (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Earthworms are an important component of soil ecosystems. The presence of earthworms in a habitat can enhance the quality of the soil, both in its physical, chemical, and biological properties. This research has the purpose to analyze the comparison of earthworm density found in natural ecosystems and artificial ecosystems. The determination of location points is done using the Cluster Sampling method, which includes both natural and artificial ecosystems. Sampling is conducted using the line transect method along a 100-meter length in 20 plots. The earthworm collection method involves the use of square and hand sorting methods. Data analysis includes density values, frequency, diversity index, and the Morisita index, as well as statistical analysis using an independent sample T-Test to determine the significance of the difference in earthworm abundance between the two locations. Five species of megadrillic earthworms were identified, classified into two ecological categories: epigeic and endogeic. In the natural ecosystem, there were five species, namely Pheretima capensis (epigeic), P. corethururus (endogeic), Pheretima sp.1 (epigeic), Megascolex sp. (endogeic), and Pheretima sp.2 (epigeic). Meanwhile, in the artificial ecosystem, three species were found, which are P. capensis (epigeic), P. corethururus (endogeic), and Pheretima sp.2 (epigeic). The density of megadrillic earthworms in the natural ecosystem (567.8 individuals/m2) is significantly higher compared to the artificial ecosystem (242.5 individuals/m2). The relative frequency of earthworms in the natural ecosystem is divided into 3 categories: Rare (Assesory), Common (Constant), and Very Common (Absolute), whereas in the artificial ecosystem, there are 2 categories: Common (Constant) and Very Common (Absolute). The diversity index of earthworms in the natural ecosystem tends to be higher (H' = 1.236) than in the artificial ecosystem (H' = 0.885). The distribution pattern of megadrillic earthworms in the natural ecosystem is clustered, while in the artificial ecosystem, it is random.